PENGGUNAAN EARLY GRADE READING ASSESSMENT (EGRA) PADA KEMAMPUAN DASAR LITERASI PESERTA DIDIK SD N 6 METRO BARAT - Siti Nurjanah; Erni; Siska Mega Diana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The lack of early reading skills among lower-grade students at SD Negeri 6 Metro Barat had become an obstacle for teachers during the learning process. In fact, early reading was a fundamental skill for students to achieve academic success in elementary school and serves as a tool for understanding the meaning of each lesson learned at school. This study aimed to analyze the use of the Early Grade Reading Assessment (EGRA) in assessing the basic literacy skills of students at SD Negeri 6 Metro Barat. This research employed a descriptive method with a qualitative approach. The sample consisted of 53 lower-grade students. Data were collected using the Early Grade Reading Assessment (EGRA) test, observation, interviews, and documentation techniques. Data analysis was conducted using non-statistical analysis. The results of this study indicated that the use of the Early Grade Reading Assessment (EGRA) in assessing the basic literacy skills of students at SD Negeri 6 Metro Barat shows variations among lower-grade students, as differentiated by the assessment aspects of the EGRA instrument. Each aspect of reading ability was interrelated and influences other reading components possessed by the students. The ability to recognize letters affects the ability to read meaningful words. The ability to read meaningful and non-meaningful words serves as an indicator of proficiency in reading aloud and understanding texts. Similarly, reading comprehension skills influence the achievement indicators in the aspect of listening comprehension.